Estrategias de marketing para promocionar la Ruta de los Hieleros de la provincia de Bolívar. año 2023. - Oña Borja, Ivonee Jacqueline (2024)
The present research focuses on developing marketing strategies to promote the Ruta of the Hieleros in the Province of Bolívar, it is based on descriptive research that allows us to know the current situation of the Ruta of theHieleros, and the approach is varied, since a survey was carried out aimed at tourists who visit the route, so that it helps us to know the differences in the supply and demand characteristics of the route to have a general vision of the situation, and it is quantitative because it measures the number of visitors who arrive at the center of the Quindigua Community, as well as the different techniques and instruments necessary to meet each proposed objective, through the use of technical observation sheets, where the main characteristics of the current Los Hieleros Route are used, such as : extensions, attractions, activities on the route. The proposed strategies were, promotion and dissemination strategies, web pages were created so that through the help of social networks their promotion and dissemination of advertising spam could occur, as well as the creation of a logo and slogan. Their digital strategies would be through loyalty strategies for users who spend the night on the route, for this, through the use of social networks on special dates such as environment day and tourism day, a type of discount will be made, where a publication will be made prior to the mentioned dates.